ANALISIS HUBUNGAN MOTIVASI KERJA DAN KEMAMPUAN KERJA DENGAN KINERJA PEGAWAI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA BATAM - Winarni, Sandra Ayu; Nurcahyant, Herbasuki; Marom, Aufarul (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2021)
This research aims to determine the relationship between work motivation and employee’s ability on employee’s performance of City Population and Civil Registry Office in Batam. This research is an explanation study using quantitative method. The respondents are 39 employees of City Population and Civil Registry Office in Batam. The research results is the correlation coefficient value of work motivation on employee’s performance using Kendall Tau rank is 0.634 with coefficient of determination value is 40.2%. The correlation coefficient value of employee’s ability on employee’s performance using Kendall Tau rank is 0.580 with coefficient of determination value is 33.64%. The concordance coefficient of work motivation and employee’s ability on employee’s performance is 0.994 sig (0.000) < α (0.005). The coefficient determination value of work motivation and employee’s ability on employee’s performance is 98,8%. The conclusion of this research is there is a positive and significant correlation between work motivation and employee’s ability on employee’s performance of City Population and Civil Registry Office in Batam. The obstacles found in this research are inadequate office facilities, and poor relations between fellow employees. The suggestions given by researcher are make the rules work in writing and clear and strengthen relationship between employees.